Mesjid dan Fungsi Teologis-Sosial: Upaya Aktualisasi Peran Remaja Mesjid: Mosque and Social-Religion Function; An Efforts to Actualize the Role of The Youth of Mosque Organization - ahmad syamsuddin; ikhwanul mu'minin (Direktorat Jenderal Bimbingan Masyarakat Islam, 2014)
Islam teaches us the principle of balance between the world and the hereafter . This principle can be seen from the function of mosque. The building that became the identity of the Muslim community is not only a place for worship like shalat and recite al-Quran, but also as place that have many function. It is shown how the Prophet Mohammad used to make the mosque not only as the central religious but also the center of military, economic, social, including enforcing the law. The Youth of Mosque Organization, the organization born from mosque institution, therefore has a significant role in addressing the ummah problems, especially young generationproblems. During this timemany youngpeople facing the problems like fights, drug abuse, and other forms of juvenile delinquency typical. Weak parental supervision and poor cultivation of religious values contributed to the delinquency trigger. The Youth of Mosque Organization need a attention from many parties . Its existence should not be underestimated, but it should be recognized and guided so that their role in fending negative behavior can be run. They need to do a variety of activities that encouraged positive impact, both of religious and social. Thus, their role gradually known by the public. Thus, the community will be pleasure to encourage their young children to become part of them